DAYA TERIMA DAN KANDUNGAN GIZI DIM SUM YANG DISUBSTITUSI IKAN PATIN (Pangasius sp.) DAN PURE KELOR (Moringa oleifera) SEBAGAI SNACK BALITA [Acceptance and Nutrient Values of Dim Sum Substituted by Patin Fish (Pangasius sp.) and Moringa Puree (Moringa oleifera) as Snack for Under Five Children] - Ni Putu Ardhanareswari (Media Gizi Indonesia, 2019)
Under five age is golden period where growth and development occurs rapidly, therefore nutrition support are important. Patin fish and Moringa leaves are foods that high in energy, and protein, which are needed in childrens growth. The purpose of this study was to analyze the infl uence of Patin fi sh (Pangasius sp.) and Moringa leaves puree (Moringa oleifera) substitution toward the acceptance and nutrient content (energy and protein) of dim sum as healthy snack for under fi ve children. This was a true experimental study with completely randomized design. Untrained panelists in this study were 30 pairs of mother and their children at integrated health post Kartini 5D to assess the acceptance of color, taste, fl avor, and texture of dim sum. Dim sum wrappers formula was F0 (0% Moringa fl our) while F1, F2, and F3 (4% Moringa fl our, 96% wheat fl our). Formula for dim sum fi lling was F0 (100% Spanish mackerel), F1 (100% patin fi sh, 0% fresh moringa leaves), F2 (90% patin fi sh, 10% fresh moringa leaves), and F3 (85% patin fi sh, 15% fresh moringa leaves). Kruskal Wallis test result on fl avor, taste, and color showed no signifi cant difference among all dim sum formulas (p>0.05), while for texture there was a signifi cant difference (p<0.037). Mann Whitney test showed that texture in control formula and modifi cation formula have signifi cant differences (p<0.05), but result the test among modifi cation formulas had no signifi cant difference. (p>0.05). Formula F2 was the best formula that can be accepted in terms of color, taste, fl avor, and texture with energy value 234 kcal, and protein 7.9 g/100 g dim sum.